Avaliação de perfil e funcionalidade de células T de memória em indivíduos curados de Tuberculose Pulmonar e com infecção latente pelo Mycobacterium tuberculosis - Marcela Miranda Tonaco (2015)
Human tuberculosis remains as one of the major causes of mortality by infectious diseases in the world. Mycobacterium tuberculosis is the main etiological agent of the disease, whose transmission occurs between people, by the inhalation of the bacillus contained in aerosols spread by the sick, as they sneeze, cough or speak. It is estimated that one third of world population is infected by M. tuberculosis. Despite the fact that 90% of these infected are able to remain in a latent state (when some bacillus are viable, but dormant), they act as a reservoir for the bacteria, because, as soon as their infection reactivates, they become a source of contamination. Although it is known that M. tuberculosis-specific T CD4+ memory cells may be induced in these individuals and in those who got cured from pulmonary tuberculosis, there are gaps about similarities and/or differences on the specific cell response between these groups, both in phenotypic level and in memory response functionality. Based on this panorama, the aim of the present study was to characterize the phenotypic profile and the functionality of T CD4+ and T CD8+ lymphocytes in individuals infected by M. tuberculosis, compared to healthy individuals and individuals who got cured from active pulmonary tuberculosis. Participants peripheral blood mononuclear cells were incubated with M. tuberculosis antigens for 144 hours; by the technique of flow cytometry, had their functionality for the production of IFN-, TNF-á and IL-2 analyzed, and were phenotypically classified regarding the expression of the cell surface markers CD45Ro and CD27. Statistical analyses of the results revealed that, within the group of latent infected individuals, immune response was characterized by predominance of T CD4+ effector cells, with significant capacity of expressing IFN-; and T CD8+ effector and T ME lymphocytes, which were capable of developing a functional response, by the expression of IFN- e TNF-á, respectively. This group showed greater proportion of T CD8+ naïve and TMC IFN-+ lymphocytes, compared to individuals cured from pulmonary tuberculosis, and also greater proportion of TMC and TME T CD8+ cells, compared to control group. In cured group no preponderance for any specific subpopulation was observed, wherein between T IFN-+ and TNF-á+ lymphocytes, predominated the phenotype only for T CD4+IFN-+, corresponding to effector T cells. In control group, effector response predominated, where most of T CD4+ lymphocytes were effector T cells, and the ones who produced more IFN- were TME lymphocytes. With regards to T CD4+, this group showed greater proportion of phenotypes TME and effector T, and TME IFN-+ cells than the other two groups. The cured ones and latent infected ones showed T CD4+ effectors and TME with greater capacity of producing IL-2 than the control group. It is expected that all date can contribute for a better comprehension of the pathophysiology and immunological modifications that occur during latent infection of M. tuberculosis, for the development of more effective vaccines and novel diagnostic methods, capable of predicting the risk of reactivation of infection, and to differentiate individuals with latent infection, patients with active tuberculosis disease and cured each other.